PROGRESSING CAVITY PUMP AS A SOLUTION TO INCREASE PRODUCTIVITY OF HIGHLY VISCOUS OIL WELLS WITH SAND PRODUCTION: A CASE STUDY OF FIELD X - Amanda Efa D; Ronaldo H.T.; Wijoyo N.D.; Steven Chandra; Prasandi AA (Scientific Contributions Oil and Gas, 2019)
Major oil fi elds in Indonesia have been experiencing massive decline in production, accompanied by excessive sand production that is not benefi cial to the integrity of the production system. Sand production has been known to increase the potential of corrosion, reducing lifetime of well equipment, and also known to shut in wells completely due to sand buildup in wellbore. Progressive Cavity Pump has been proposed as a solution to withstand these complications, due to its nature that can handle many types of fl uids and even produced solid. The idea is then tested to a mature Alabaster fi eld where the majority of the wells have been shut in due to excessive sand problem and low productivity. It is worth nothing that after installing the PCP, production modeling indicates possibility of sustaining production through the application of PCP, where the production increases around 120 STB/ day. Although PCP has proven its effectiveness, it is important to note that auxiliary sand mitigation techniques is required to maintain facilities integrity after several years of production.